2010
DOI: 10.1039/c004762g
|View full text |Cite
|
Sign up to set email alerts
|

A clean and effective supercritical carbon dioxide method for the host–guest synthesis and encapsulation of photoactive molecules in nanoporous matrices

Abstract: The present work is concerned with host-guest processes in the micro-and mesoporous restricted spaces provided by silica aerogels and aluminosilicates. A supercritical carbon dioxide ship-in-a-bottle approach was used for the synthesis of photoactive molecules (triphenylpyrylium and dimethoxyltrityl cations) inside these nanoporous matrices. The resulting hybrid nanocomposites can act as stable and recoverable heterogeneous photocatalysts, having obvious advantages with respect to the more easily degraded orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Evacuation of solvents in supercritical conditions is commonly used to produce aerogels which is a term given to open pore materials presenting low density and large specific surface area. The most known aerogels are silica, (Murillo-Cremaes et al 2010;Moner-Girona et al 2003;Martin et al 2008;Budunoglu et al 2011) carbon, (Wu et al 2013;Mecklenburg et al 2012) organic-inorganic aerogels (Hendel et al 2013;Ennajih et al 2012) and more recently thick pieces of BC aerogels have also been reported (Hendel et al 2013;Liebner et al 2010;Cai et al 2008;Russler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evacuation of solvents in supercritical conditions is commonly used to produce aerogels which is a term given to open pore materials presenting low density and large specific surface area. The most known aerogels are silica, (Murillo-Cremaes et al 2010;Moner-Girona et al 2003;Martin et al 2008;Budunoglu et al 2011) carbon, (Wu et al 2013;Mecklenburg et al 2012) organic-inorganic aerogels (Hendel et al 2013;Ennajih et al 2012) and more recently thick pieces of BC aerogels have also been reported (Hendel et al 2013;Liebner et al 2010;Cai et al 2008;Russler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Application areas include, among others: (1) the use of supercritical fluids to modify porous materials, [1][2][3][4] (2) physical adsorption of trace components from gaseous effluents, 5 (3) gas storage using microporous materials, 6 and (4) chemical separations using inorganic membranes. Application areas include, among others: (1) the use of supercritical fluids to modify porous materials, [1][2][3][4] (2) physical adsorption of trace components from gaseous effluents, 5 (3) gas storage using microporous materials, 6 and (4) chemical separations using inorganic membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of properties in porous materials is of continuing interest in the fields of chemical and materials engineering. Application areas include, among others: (1) the use of supercritical fluids to modify porous materials, [1][2][3][4] (2) physical adsorption of trace components from gaseous effluents, 5 (3) gas storage using microporous materials, 6 and (4) chemical separations using inorganic membranes. 7 The confinement of a fluid in a porous matrix changes its properties relative to its bulk state and this may be important in engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…First, the null surface tension of a supercritical fluid allows the 80 drying of alcogels preserving their porosity to form aerogels (Wagh et al, 1999;Yoda and Ohshima, 1999). Second, due to the low viscosity and high 81 diffusivity of fluids under supercritical conditions, scCO2 solutions have the ability to penetrate and efficiently impregnate porous matrices with organic 82 solutes, in this work selected model drugs, again without damaging the porous structure (Domingo et al, 1998;Murillo-Cremaes et al, 2010). 83…”
Section: Introduction 28mentioning
confidence: 99%